Urban wastewater reuse for crop production in the water-short Guanajuato River Basin, Mexico - Scott, Christopher A.; Zarazua, J.A.; Levine, G. (International Water Management Institute, 2000)
From a river-basin perspective, wastewater irrigation is an important form of water and nutrient reuse; however, there are important water quality, environmental, and public health considerations. This report explores the advantages and risks of urban wastewater reuse for crop production in the water-short Guanajuato river-basin in west-central Mexico, and then by a selective literature review demonstrates how common this practice is worldwide. It also evaluates several alternative water-management scenarios through application of the Interactive River Aquifer Simulation (IRAS) model, developed by Cornell University and Resource Planning Associates.